2014
DOI: 10.1111/1440-1681.12263
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced external counterpulsation improves endothelial function and exercise capacity in patients with ischaemic left ventricular dysfunction

Abstract: Enhanced external counterpulsation (EECP) therapy decreases angina episodes and improves quality of life in patients with left ventricular dysfunction (LVD). However, studies have not elucidated the mechanisms of action and overall effects of EECP in patients with LVD. The purpose of this study was to investigate the effects of EECP on endothelial function in peripheral conduit arteries and exercise capacity (peak VO2) in patients with LVD. Patients with ischemic LVD (EF 34.5±4.2%; n=9), and patients with symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
1
27
0
1
Order By: Relevance
“…In addition, we did not measure shear rate area under the curve until peak FMD which may under represent nFMD measures (Pyke et al 2004). However, the methods employed herein were performed, in part, for consistency with our previously published work on the effects of EPC interventions on FMD (Braith et al 2010;Beck et al 2014). Finally, indices of sympathetic nervous system (SNS) activity were not measured in the present study, and consequently the effects of SNS modulation in response to EPC cannot be ruled out.…”
Section: Experimental Considerations and Future Directionsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, we did not measure shear rate area under the curve until peak FMD which may under represent nFMD measures (Pyke et al 2004). However, the methods employed herein were performed, in part, for consistency with our previously published work on the effects of EPC interventions on FMD (Braith et al 2010;Beck et al 2014). Finally, indices of sympathetic nervous system (SNS) activity were not measured in the present study, and consequently the effects of SNS modulation in response to EPC cannot be ruled out.…”
Section: Experimental Considerations and Future Directionsmentioning
confidence: 98%
“…A single 45 min EECP session has been shown to acutely increase flow-mediated dilation (FMD) (Gurovich and Braith 2013), a surrogate of conduit artery endothelial function and nitric oxide bioavailability (Akhtar et al 2006). Chronically, administration of EECP has been shown to elicit significant improvements in FMD of the brachial (Hashemi et al 2008;Braith et al 2010;Beck et al 2014), femoral (Braith et al 2010;Beck et al 2014), and popliteal arteries . Moreover, resistance artery blood flow and reactivity (e.g., peak reactive hyperemic blood flow) is significantly improved following chronic EECP administration in clinical (coronary artery disease) and pre-clinical (abnormal glucose tolerance) patients (Braith et al 2010;Avery et al 2014;Martin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cuffs were inflated at a high pressure (up to 300 mmHg), which greatly altered arterial physiological hemodynamics [19], blood flow was retrograde and turbulent in the femoral artery but anterograde and laminar in the brachial artery [20]. Nevertheless, Gurovich et al [21] have shown, in a study that included 18 young men (25±4 years), that a single 45-min session of EECP with a pressure of 250 mmHg increased FMD in the femoral and brachial arteries compared with baseline, despite different blood flow patterns (retrograde-turbulent blood flow in the femoral artery and anterograde-laminar blood flow in the brachial artery).…”
Section: Discussionmentioning
confidence: 99%
“…Beck et al [20], described EECP duration of thirty-five 1-hour sessions (5 days a week for 7 weeks) with inflation pressures of 300 mmHg, in patients with ischemic left ventricular dysfunction, and showed improvement of brachial and femoral artery endothelial function. The pulsatile inflatable suit in our study was used with cuffs inflated at a value below the diastolic blood pressure.…”
Section: Amah Et Al Remote Enhancement Of Skin Blood Flowmentioning
confidence: 99%
“…с соавт. продемонстрировали значимое улуч-шение поток-зависимой вазодилатации у пациентов с ишемической дисфункцией левого желудочка и ста-бильной стенокардией (+50% и +74%, соответствен-но) после курса УНКП (35 часовых процедур) [13]. Это сопровождалось и значимым повышением уровней нит-рата/нитрита в плазме (+55% и +28%), простациклина (+50% и +70%), а также пиковым потреблением кис-лорода (Vo 2 +36% и +21%) в обеих группах.…”
Section: Enhanced External Counterpulsation In Clinical Practice усилunclassified